CaMKLL regulation of phospholamban and SR Ca2 load - Mattiazzi, Ramona Alicia (2011)
Phospholamban (PLN) is a small phosphoprotein in the cardiac sarcoplasmic reticulum (SR). Dephosphorylated PLN tonically inhibits the SR Ca2 -ATPase (SERCA2a), and phosphorylation of PLN, at either Ser16 by PKA or Thr17 by Ca2 - calmodulin–dependent protein kinase (CaMKII), reverses this inhibition. Consequently, there are increases in SERCA2a activity, SR Ca2 uptake rate, and SR Ca2 load. Through this mechanism, PLN is a major regulator of basal cardiac Ca2 cycling, contractility, and relaxation and the main determinant of -adrenergic mechanical responses in the heart. In this article, we briefly review the functional role of CaMKII-dependent PLN phosphorylation at the Thr17 site and the new findings that link this phosphorylation to beneficial or detrimental effects in pathophysiological situations.